2018
DOI: 10.1002/dta.2518
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of insulin and insulin analogs from dried blood spots by means of liquid chromatography–high resolution mass spectrometry

Abstract: While dried blood spot (DBS) analysis concerning low molecular mass molecules has become more and more established in various fields of analytical chemistry, the utility of DBS in determining peptides and proteins from DBS is yet comparably limited. In consideration of the fact that the apparent benefits of DBS sampling are similar for analytes of lower and higher molecular mass, dedicated (non-generic) sample preparation procedures are required that meet the needs for detecting peptidic drugs and hormones in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Another example for the expanding utility of DBS for routine doping controls was presented by Thomas et al, who demonstrated the applicability of the minimally invasive sampling technique to the analysis of insulin and insulin analogs . Employing citric acid‐pretreated DBS collection cards, spots of 20 μL volume were collected and subjected to an extraction protocol consisting of excising the entire spot, which was then extracted twice into 200 μL of a mixture of acetonitrile/3% acetic acid (60/40, v/v) and both volumes were combined and diluted with water prior to SPE.…”
Section: Hormone and Metabolic Modulatorsmentioning
confidence: 99%
“…Another example for the expanding utility of DBS for routine doping controls was presented by Thomas et al, who demonstrated the applicability of the minimally invasive sampling technique to the analysis of insulin and insulin analogs . Employing citric acid‐pretreated DBS collection cards, spots of 20 μL volume were collected and subjected to an extraction protocol consisting of excising the entire spot, which was then extracted twice into 200 μL of a mixture of acetonitrile/3% acetic acid (60/40, v/v) and both volumes were combined and diluted with water prior to SPE.…”
Section: Hormone and Metabolic Modulatorsmentioning
confidence: 99%
“…Dried blood spots (DBSs) are a promising sample collection strategy, which could complement the current strategy of urine and blood analysis for anti-doping. Applications have been demonstrated for many substances on the WADA Prohibited List, for in-and out-of-competition use (S0-S5 and M1-M3) and in-competition use (S6-S9, P1) 1 : S1 anabolic agents, 2,3 S2 peptides, hormones, growth factors, related substances and mimetics, [4][5][6][7][8][9][10] S3 beta agonists, 11 S4 hormone and metabolic modulators, 12,13 S5 diuretics and masking agents, 11 S6 simulants, 14 S7 nacotics, 15,16 S8 cannabinoids, 17 S9 glucocorticoids, 18 P1 beta-blockers, 11 and M1 manipulation of blood and blood components. [19][20][21] In October 2019, the World Anti-Doping Agency (WADA) together with seven anti-doping organizations (ADOs) announced the development and implementation of DBS testing for routine analysis in time for the 2022 Winter Olympic and Paralympic Games in Beijing.…”
Section: Introductionmentioning
confidence: 99%
“…Dried blood spots (DBS) appear attractive as an alternative sample matrix for antidoping purposes due to the minimal invasiveness, potentially reduced costs for collection and transportation, 11 and the possibility to detect a wide range of doping substances. [11][12][13][14][15][16][17][18][19][20] While clenbuterol is detectable in DBS when it is added directly to the DBS card (i.e. a spiked DBS sample), 12 it is unexplored if and for how long the drug can be detected in DBS samples obtained from humans after clenbuterol ingestion.…”
Section: Introductionmentioning
confidence: 99%